Effect of SnO2/Al2O3 ratio of Si-based MFI on its acidity and hydrophobicity: application in selective hydroxyalkylation of p-cresol - Garade, Ajit C.; Malwadkar, A. V.; Niphadkar, P. S.; Jha, Ratnesh Kumar; Joshi, P. N.; Rode, C. V. (Catalysis Communications, 2014)
Silica based MR type molecular sieves with various SnO2/Al2O3 ratios were synthesized from gels having molar compositions SiO2:xSnO(2):yAl(2)O(3):0.23(TPA)(2)O:35H(2)O where 0 <= x <= 0.02 and 0 <= y <= 0.01. Recyclable, Al-free Sn-MFI catalyst showed 31% conversion of formaldehyde with 100% selectivity to 2,2'-methylenebis(4-methylphenol) in hydroxyalkylation of p-cresol with formaldehyde on account of moderate acidity and higher hydrophobicity. (C) 2013 Elsevier B.A. All rights reserved.
Keywords: Al-27 MAS NMR; Hydroxyalkylation; Molecular sieves; p-Cresol; Stannosilicate